Evaluation of Inter-Scale Parameters in Dementia Village Design Through Examples - Nisa Nur Göksel; Nuriye Nida Çelebi Şeker (Senectus)
In European countries, various policies and projects are being developed and implemented to meet the needs of the aging population. These projects also explore solutions for elderly dementia patients as a disadvantaged group. Dementia villages are designed to enable elderly patients to live together, retain independence, and remain in familiar environments, which may help slow or stabilize disease progression. This study identifies inter-scalar design criteria through dementia villages and conducts visual analyses of selected projects. Since it was the first project of its kind, the Hogeweyk Dementia Village was examined, and nine other projects modeled after it were included in the sample. The study follows a four-stage qualitative research design. The first stage involved a literature review, the second stage established design parameters, the third stage conducted content and visual analyses, and the final stage presented the findings. The results indicate that dementia villages should meet design needs including spatial form, circulation planning, comfort conditions, safety, esthetics, autonomy, socialization, and privacy.